ANALISIS FAKTOR-FAKTOR YANG MEMPENGARUHI MOTIVASI WISATAWAN DALAM MELAKUKAN WISATA HERITAGE DI KAWASAN BRAGA KOTA BANDUNG - Sudaryanti, Irma Juni (2015)
Tourist's motivation is affected by push factor and pull factor. Push factor is elements that sourced from inside the tourist itself. Whereas, pull factor is elements that sourced from outside the tourist itself, generally from condition of the destination that will be visited. Each tourist has different influence factor of motivation in having tourism. Having a different tourism will enact a different influence factor of motivation. One of it is heritage tourism. Bandung is having many potential heritage tourism site, one of them is Braga. Buildings of Dutch Government inheritance sturdily exist in this Braga area. Research method used in this research is descriptive method with quantitative approach. Analytical tool used in this research is factor analysis. The outcome of questioner then be analyzed by factor analysis. The output of the analysis then be described for having images of influence factor of tourist's motivation in visiting heritage tourism site. The output of this research are: there are 4 (four) new factors that influencing tourist's motivation in visiting heritage tourism site. With 1 (one) dominant factor which has the highest eigen value amongst the other factors.